Design of a vacuum system for space active hydrogen maser - Que, Haohui; Xu, Wujiabei; Li, Qi; Xiang, Jie; Lu, Tao; Liu, Tiexin; Cai, Yong; Dai, Jiayu; Hou, Xueling (Frontiers in Physics, 2022)
With the high precision and stability of its frequency signal outputs, active hydrogen maser plays an important role in fields such as timing, satellite navigation and communication. However, it needs to be lighter so as to be applied in space. We made a research, based on the computation of the hydrogen flow and the adsorption efficiency of the adsorption unit, on the parameters of the vacuum system and the structural requirements, and designed a combined vacuum pump for the space active hydrogen maser (SAHM). This vacuum pump, which has a total mass of about 5kg, and is much lighter than the ground ones, consists of a getter pump and a small ion pump. The pumping speed will be about 474 L/s by computation, when an amount, 2.5 MPa⋅L, of hydrogen having been adsorbed by getters. Theoretically, the design should fully meet the requirements of the SAHM vacuum system, since the total source hydrogen inflow in lifetime is not higher than 20% of the total capacity getter pump. The work is of great significance for future SAHM applications.